Perbedaan Tekanan Darah Sebelum dan Sesudah Pekerja Kopi Terpajan Kebisingan di Penggilingan Padi - Muhammad Amin; Rita Rosari; Yenida Yenida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine differences in blood pressure before and after workers exposed to noise in rice and coffee milling in Kepahiang Regency. This research was conducted in July 2017 with quantitative research type and research design which used pre experimental design with one group pretest posttest approach. The sampling technique used is total sampling with sample is 22 workers at point 1 had increased sistole blood pressure (39.29%) and 17 workers at point 2 did not increase Sistole blood pressure (30.36%). While for diastolic blood pressure, there were 14 workers at point 1 had an increase in diastolic blood pressure (25%) and 18 workers point 2 did not increase diastolic blood pressure (30%). Based on Wil Coxon Signed Ranks Test statistical results obtained p = 0.000 <α (0.05) for blood pressure of laborer systole point 1, p = 0.000 <α (0.05) for blood pressure sistole worker point 2, p = 0.000 <α (0.05 ) for diastolic blood pressure point 2, and p = 0.002 <α (0.05) for the worker's diastolic blood pressure at point 2. So there is a significant difference in blood pressure before and after workers exposed to noise in rice and coffee milling in Kepahiang Regency. Keywords: Blood Pressure, Noisy